Breast Region Segmentation and Pectoral Muscle Removal in Mammograms - M. Slavković-Ilić (Telfor Journal, 2016)

(untitled)
The first step in most computer aided diagnosis systems is an accurate segmentation of breast region, which affects not only the accuracy but also the speed of the analysis because it significantly reduces the area of the image to be examined. The second step usually includes removal of pectoral muscle region, which is seen in mediolateral oblique view mammograms. This is primarily done to reduce the number of false positive breast cancer detections. In this paper, a method for the segmentation of breast region based on contrast enhancement and k-means algorithm is proposed. To extract pectoral muscle, a region of interest is found, its contrast is enhanced and the pectoral muscle is identified using k-means algorithm. Cubic polynomial fitting is used for the estimation of muscle's boundary. The method is validated with mammograms from miniMIAS database.